Vietnamese upper-high school teachers’ views, practices, difficulties, and expectations on teaching EFL writing - Nguyen Thi Thuy Hang (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
Teaching EFL writing at the secondary level of education is one of the challenging tasks for every teacher. However, few studies on how EFL writing is taught at up-secondary schools (U-SS) have been reported. This study attempts to explore how Vietnamese teachers at this educational level perceived the importance of EFL writing, how they taught this skill, and what difficulties and expectations/suggestions they had in making the teaching of this skill at their own schools more effectively. Employing the 5-point Likert-scale survey with 20 teachers from five U-SS, classroom observations, and semi-structured interviews, the study found these teachers' understanding of the importance of teaching this skill, their confidence, and appropriate pedagogical use and content knowledge (PCK) in teaching it. However, their lack of time, the heavy contents in the textbooks, the multiple-choice test formats, large classes, students' dislike of this skill, and their insufficient knowledge of grammar and vocabulary challenged their teaching of this skill. With the suggestions/recommendations made by these teachers, this study is expected to provide some insights for relevant and timely support to teachers for the effectiveness of teaching this skill in the educational settings in Vietnam and in similar EFL contexts.